2017
DOI: 10.1016/j.jccw.2018.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Burn Injury from a Wedding Ring: An Unusual Case

Abstract: Thermal ring injuries are rarely reported in the literature. For this reason, treatment is varied without a standard approach. We describe a case of a thermal wedding ring injury sustained during a welding accident. It is critical to understand the 3 zones of burn injuries when managing these infrequent cases. Furthermore, the dynamic progression that ensues a thermal burn will directly affect outcome. A case is presented along with a graduated approach to the management of such injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Macroscopic, microscopic, and electron microscopic studies of the atria and auricles of intact guinea pigs have shown that they have general features of structure [13,14]. Complex studies have shown that the nature and degree of damage of the parts of the heart depended on the duration of the experiment and increased according to the stages of thermal trauma [15].…”
Section: Methodsmentioning
confidence: 99%
“…Macroscopic, microscopic, and electron microscopic studies of the atria and auricles of intact guinea pigs have shown that they have general features of structure [13,14]. Complex studies have shown that the nature and degree of damage of the parts of the heart depended on the duration of the experiment and increased according to the stages of thermal trauma [15].…”
Section: Methodsmentioning
confidence: 99%
“…Electrical or chemical hand injuries are associated with high morbidity. Generally, second or third-degree hand burns are considered a major burn injury, and it is mandatory to refer them to the burn center [1][2][3]. Contracture following hand burns is common, and movement limitations could decrease quality of life, significantly.…”
Section: Introductionmentioning
confidence: 99%
“…The term recovery of the burned skin determines the course of burn disease, the formation of complications, the cosmetic effect. It is known that deep and large thermal burns are not limited only to local damages of tissues, but also cause significant violations of all systems and organs, metabolic processes in the body [1,2,4,6]. The primary link in the pathogenesis of burn disease is the destruction of the skin, significant hemodynamic disorders and violation of neuroendocrine regulation [6,12,14].…”
Section: Introductionmentioning
confidence: 99%